Intelligent system of duo functional bagpack - Imran, H.; Zulfadhli, S.M.; Qibtiah, Raja Mariatul; Rani, Ridhwan; Azraai, Munirah Ahmad (2020)
In today’s world, numerous technological innovations have been introduced to improve the performance of human intelligence. While some tasks can be accomplished conventionally, many tasks become easier when technology is integrated. The internet of things is a critical component of intelligent technologies nowadays. One of these innovations is the ‘smart bagpack’ that will be useful for travelers. This study aims to develop an android application to track the location of a backpack. The structure integrates a GPS receiver that records the bag's longitude and latitude. This position is accessible via an SMS message sent to another user. Together with assistance of coordinates information, provided by GPS, the user will able to locate the bag using Google Map. Once the device is in standby mode, the authorized user will get a notification message when the Bluetooth has been disconnected, and the user will sound the buzzer to locate the bag. Furthermore, this product will make it easier for users to answer phone calls while on the move. A button on the backpack will be connected to the phone by Bluetooth to make sure the user can access an android application to answer the call. The backpack will send alerts on incoming calls, and the user can answer with the push of a button without ever taking out the phone. This could help solve problems faced by commuters when trying to receive voice calls during peak travel hours. This project consists of two main features, which are tracking and call pick up.